« French belongs to no one, French belongs to everyone ». Sur l’attractivité de la littérature médiévale aux États-Unis - Marion Uhlig (Perspectives Médiévales)
Academic positions as well as Master degrees in Medieval French language and literature have become more and more rare in The United States. It is therefore urgent to think of possible ways to stimulate the interest of students in order for them to take over in the future. But how to increase the attractiveness of Medieval literature in French when it doesn’t belong to the students’ cultural heritage? This testimony reviews the potential solutions that my colleagues and I considered during my stay as Assistant Professor of Medieval French at the University of Wisconsin-Madison between 2013 and 2015. Two points are essentially at stake: on the one hand, the languages in which Medieval texts are read and taught – either Modern French for both or, respectively, Old French and English – and, on the other hand, the keen interest of researchers and students toward Global Studies and francophone literature that both entertain links with Medieval literature in French.